A double-edged sword: unusual multiple severe infections with pralsetinib: a case report and literature review - Poumeaud, François; Jaffrelot, Marion; Gomez-Roca, Carlos; Korakis, Iphigénie; Leonardi, Giulia; Joly, Marine; Mazières, Julien; Guimbaud, Rosine; Fares, Nadim; Alouani, Emily (Frontiers in Medicine, 2024)
SelecTve RET tyrosine kinase inhibitor, pralseTnib, demonstrated clinical efficacy and was well tolerated in lung and thyroid cancers with RET gene mutaTons or fusions in clinical trials. While the lader focused on the risk of pneumoniTs, there is scarse data regarding other type of infecTous risk on pralseTnib. Herein, we report the case of a 53-year-old paTent with CCDC6-RET fusion neuroendocrine tumor, who achieved parTal response with pralseTnib as fifh line therapy. Of parTcular note, during pralseTnib therapy, his clinical course was complicated by five severe infecTous episodes including two oxygen-requiring pneumonias, two disTnct spondylodisciTs and one pneumocysTs. Our study highlights the increased risk of any type of opportunisTc infecTous event with pralseTnib, but not selpercaTnib, probably caused by offtarget JAK1/2 inhibiTon.